PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 028 SRIKAYANGAN - Mutiara S, Herlina; Noviana, Eddy; ', Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: intent deep observational it is subject to be increase IPA studying result student class IV SD Negeri 028 Srikayangan passes through learning model implements kooperatif types Snowball Throwing . Observational form that is utilized is observational action braze. On action research brazes this researcher plot action and action result reflection. Action performing did by acting researcher as teacher up to learning process. Activity result learns on meet i. cycle first which is 54,54% by enough categories, then increasing on appointment second becomes 63,64% get categories well. On cycle II. appointment first increases 72,73% by good categories, then on appointment second increases again 90,91% by pretty good categories. Student activity result on meet i. cycle percentage first 61,11% get categories well, then on second appointment 66,67% also get categories well, on cycle II. first appointment 86,11% get categories very good, on second Cycle appointment II. also experience step-up 94,44% by ketegori very good. Meanwhile on cycles daily dry run II. experience thoroughness step-up, complete student 24 person, meanwhile that don't complete 2, with klasikal's thoroughness 92,30% (complete). Thus therefore gets to be concluded that with learnings model implement kooperatif type Snowball Throwing can increase IPA'S studying result student brazes IV. SD Negeri 028 Srikayangan corresponds to action hypothesises.Key Word: Kooperatif Model Type Snowball Throwing, IPA Learned Result